Penggunaan Media Google Sites dalam Menunjang Pembelajaran Menulis Puisi di Kelas VIII SMP Negeri 4 Palembang - Aulia Novianti; Nuzula, Khalidatun; Hani Atus Sholikhah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to develop learning media based on Google Sites to improve the poetry writing skills of grade VIII junior high school students. The background of this research is based on the low interest and effectiveness of conventional learning in teaching poetry, as well as the need for interactive and digital media. The method used is research and development with the Alessi and Trollip model which includes planning, designing, and developing stages. The media was developed based on the results of the needs analysis of students and teachers, and validated by media, material, and language experts. The validation results showed that this media obtained a very good feasibility score, with an average percentage of 86.35%. This finding indicates that Google Sites is effective as a poetry learning media that is able to integrate visual, audio, and interactive elements to support students' writing skills. This research contributes to the development of digital literacy in secondary schools and offers contextualized and fun learning solutions.